Effects Of Molar Ratio Of Iron Catalyst On Synthesis Of Carbon Nanotubes Via Catalytic Chemical Vapor Deposition - Toussi, Setareh Monshi (2010)

(untitled)
Research on the area of the synthesis of carbon nanotubes is fundamental and critical to the entire subject of carbon nanotubes. This dissertation describes an experiment to synthesize carbon nanotubes by the method of catalytic chemical vapor deposition (CCVD). It focuses on the relationship between the as-prepared catalyst and the synthesized carbon nanotubes. The effect of growth parameters for the synthesis of carbon nanotubes was also studied. The Fe-Mo-MgO catalysts with five different molar ratios of iron (Fe) in this composite catalyst were prepared through the impregnation method. The goal of this work was to identify the suitable molar ratio of iron (Fe) in the composite catalyst of Fe-Mo-MgO on which carbon nanotubes (CNTs) can be grown with a higher yield and quality.Scanning electron microscopy (SEM), transmission electron microscopy (TEM), xray diffraction (XRD), and thermogravimetric analysis (TGA) were used to characterize the as-prepared catalysts and as-grown carbon nanotube samples. Among these catalysts with different molar ratio of iron, the main and obvious observation in the synthesis of carbon nanotubes was the yield of synthesized carbon nanotubes. That is, increasing the molar ratio of iron, the yield of produced carbon nanotubes increases strongly, but the quality did not improve. While by decreasing the Fe concentration, both the structural defects and yield were reduced. Therefore, based on the experimental results, the best catalyst was catalyst 3 (Fe: Mo: MgO = 0.5: 0.1: 10) with a moderate molar ratio of iron. This catalyst not only had good yield but also good quality. The different parameters such as flow rate of argon (Ar) as a carrier gas, and temperature to improve the growth condition of CCVD method for the synthesis of CNTs by Fe-Mo-MgO catalyst were examined. It is found that the best flow rate for carrier gas is 100 ml/min. For the flow rate lower or higher than this, there were very few CNTs formed, since the low flow rate of Ar could not carry enough ethanol vapors through the reactor to be deposited on the catalyst. As for the high flow rate of Ar, most of the carbon source exited from the outlet of the reactor and again they could not be deposited on the catalyst, thus few carbon nanotubes were formed. In the synthesis of carbon nanotubes by CCVD method, the temperature plays a key role. The results show that when the temperature is lower than 750°C, few CNTs were formed, and when the temperature is higher than 900°C, more and more amorphous carbons were formed in the CNTs. The best temperature for the growth of carbon nanotubes by these catalysts is between 800°C and 900°C. The results showed that the growth of carbon nanotubes was significantly influenced by the reaction condition due to its sensitivity. The synthesis products were always a mixture of single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs).